Pelatihan Manajemen Media bagi Pengelola Media Sosial Lembaga Pendidikan - Moh. Samsul Arifin (STIT Al - Ibrohimy Bangkalan, 2025)
This community service activity aims to enhance the capacity of social media managers in educational institutions within Galis Subdistrict to utilize digital media effectively and professionally. The background of this program stems from the limited understanding among education personnel regarding content management strategies, social media algorithms, and digital ethics. The training was conducted through workshops, case study discussions, and direct mentoring. The training materials covered content strategies, branding, digital security, and the use of platforms such as Facebook, Instagram, and TikTok. The results indicated an increased understanding of social media management among participants, improvements in content quality, and enhanced digital interaction between educational institutions and the community. Another positive impact was the growing awareness of digital ethics and more targeted communication strategies. This activity serves as a concrete contribution to the implementation of the Tri Dharma of Higher Education, particularly in the field of community service.